Rapid testing of SARS-CoV-2 antibodies: Report of an experience in an Emergency Service - Collins-Camones, Jaime Antonio (2020)
Objective: To determine the positivity and patterns of positive results of rapid antibody tests against SARS-CoV-2 in patients attending to an Emergency Service. Material and methods: Retrospective evaluation of the rapid antibody tests against SARS-CoV-2 applied during the month of June 2020 in the Emergency Service of the Hospital EsSalud G.Almenara, Lima, Peru. Results: We included 1805 tests performed on the same number of patients. In 864 (48%) of the tests were positive, in the following order: combined IgM-IgG pattern in 635 (73%), IgM in 134 (16%) and finally IgG in 95 (11%). Conclusions: The positivity of the rapid antibody tests against SARS-CoV-2 was 48%, and the combined pattern of IgM-IgG was the most frequent in three quarters of the confirmed cases.